Italian Children’s Well-Being after Lockdown: Predictors of Psychopathological Symptoms in Times of COVID-19 - Marcella Caputi (MDPI AG, 2021)
The first Italian lockdown imposed to fight the spread of COVID-19 caused important disruptions in families’ everyday lives. The main aim of this research was to investigate the predictors of psychopathology in children aged 5–10 years, immediately after the national 2-month lockdown. A total of 158 Italian parents (148 mothers, 10 fathers, mean age = 41 years) were recruited and asked to complete an online research concerning their 158 children (76 boys, mean age = 7.4 years). Parents completed questionnaires on parent–child conflict, resilience, temperament, behavior, and previous adverse childhood experiences. Hierarchical regressions showed that children’s psychopathology was predicted by low child resilience, high novelty seeking and harm avoidance, adverse experiences, and high flooding levels. Moreover, girls exposed to adverse experiences appeared more vulnerable to psychopathology. The recruitment of a convenience sample, the small sample size, and the cross-sectional design of our study limit the generalizability and interpretation of the present findings. Nonetheless, this research extends our knowledge of children’s functioning in such an exceptional period. Shedding light on predictors of children’s psychopathology following prolonged quarantine can indeed guide effective psychological interventions now and in future similar situations.